Immunization in End‐Stage Renal Disease: Opportunity to Improve Outcomes. Issue 4 (10th June 2013) - Soni, Ritu; Horowitz, Bruce; Unruh, Mark
Abstract Infection is the second most common cause of death in patients with end‐stage renal disease (ESRD), following cardiovascular causes. Immunization is a fairly simple, but underutilized, strategy for prevention of infectious morbidity and mortality in patients with kidney failure. It is imperative for nephrologists and primary care providers to have an understanding of immunization as an essential component of preventive healthcare measures in this high‐risk population. Patients with ESRD represent a unique population due to their immunosuppressed state, dialysis‐related exposures and suboptimal response to routine vaccines. While the Advisory Committee on Immunization Practices (ACIP) provides guidelines for vaccination of patients with renal disease against Hepatitis B, influenza and pneumococcal disease, the data on immunization against other commonly preventable infectious diseases are lacking. This article reviews the recent evidence on immunization in the ESRD population and synthesizes the related implications for maximizing prevention of infectious diseases in this high‐risk population.